Programmable co-delivery of the immune checkpoint inhibitor NLG919 and chemotherapeutic doxorubicin via a redox-responsive immunostimulatory polymeric prodrug carrier - Sun, Jing-jing (Acta Pharmacol Sin, 2017)
To achieve synergistic therapeutic efficacy and prevent cancer relapse, chemotherapy and immunotherapy have been combined as a new modality for tumor treatment. In this work, we designed a redox-responsive immunostimulatory polymeric prodrug carrier, PSSN10, for programmable co-delivery of an immune checkpoint inhibitor NLG919 (NLG) and a chemotherapeutic doxorubicin (DOX). NLG-containing PSSN10 prodrug polymers were self-assembled into nano-sized micelles that served as a carrier to load DOX (DOX/PSSN10 micelles). DOX/PSSN10 micelles displayed spherical morphology with a size of ∼170 nm. DOX was effectively loaded into PSSN10 micelles with a loading efficiency of 84.0%. In vitro DOX release studies showed that rapid drug release could be achieved in the highly redox environment after intracellular uptake by tumor cells. In 4T1.2 tumor-bearing mice, DOX/PSSN10 micelles exhibited greater accumulation of DOX and NLG in the tumor tissues compared with other organs. The PSSN10 carrier dose-dependently enhanced T-cell immune responses in the lymphocyte-Panc02 co-culture experiments, and significantly inhibited tumor growth in vivo. DOX/PSSN10 micelles showed potent cytotoxicity in vitro against 4T1.2 mouse breast cancer cells and PC-3 human prostate cancer cells comparable to that of DOX. In 4T1.2 tumor-bearing mice, DOX/PSSN10 mixed micelles (5 mg DOX/kg, iv) was more effective than DOXIL (a clinical formulation of liposomal DOX) or free DOX in inhibiting the tumor growth and prolonging the survival of the treated mice. In addition, a more immunoactive tumor microenvironment was observed in the mice treated with PSSN10 or DOX/PSSN10 micelles compared with the other treatment groups. In conclusion, systemic delivery of DOX via PSSN10 nanocarrier results in synergistic anti-tumor activity.